(untitled) - Diffie, Bailey W. (Minneapolis, 1977)
This important multi-volume series provides a scholarly, analytical, historical account of European expansion and the world from the fourteenth to the twentieth century.
Keywords: Portugal,Bồ Đào Nha; History,Lịch sử; 1385-1580,1385-1580